2009
DOI: 10.1097/rli.0b013e31819dcc84
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging as Predictor of Therapy Response in an Animal Model of Ewing Sarcoma

Abstract: Compared with volumetric measurements, DWI of the viable tumor parts could be used to discriminate between the effects of 2 different dosages at an earlier time point than volumetric measurements in an animal model in vivo. This method could be especially useful for monitoring drug effects in phase I/II clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Hence, molecular imaging with DW-MRI is an alternative imaging approach to monitor cancer therapy, as has been shown e.g. for experimental Ewing sarcoma (35). We were unable to detect any substantial differences in tumor ADCmean 1 d or 2 d after a single dose of gemcitabine in either of the lung tumor models investigated here (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…Hence, molecular imaging with DW-MRI is an alternative imaging approach to monitor cancer therapy, as has been shown e.g. for experimental Ewing sarcoma (35). We were unable to detect any substantial differences in tumor ADCmean 1 d or 2 d after a single dose of gemcitabine in either of the lung tumor models investigated here (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…The analysis of DW imaging data for this application should not be qualitative but rather rely on quantitative changes between the pretreatment and posttreatment images with measurement of the ADCs. Several reports have addressed the utility of DW imaging in the assessment of treatment response and have shown that ADCs correlate well with response in primary bone sarcomas in human patients (36,39,80,113) and in animal models (35,40,43). In soft-tissue sarcomas (18,22,45), ADC changes have been shown to correlate with tumor volume (22) and treatment response (18,45) (Fig 2).…”
Section: Prediction Of Treatment Response Following Neoadjuvant Therapymentioning
confidence: 99%
“…DW imaging has also been used for characterizing changes in the surgical bed in patients examined for evaluation of the possibility of recurrent tumor (23). Furthermore, DW imaging is well suited to the study of a sarcoma after neoadjuvant therapy to determine whether treatment-related necrosis has occurred in a tumor (19,22,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Where cytotoxic edema develops (eg, in areas of treatment-related necrosis with changes to the dependent sodium-potassium pumps across the cell membrane), there will be increased water mobility, as compared with areas where tumor cellularity is maintained (eg, nonresponsive tumors) (46).…”
Section: Dw Imaging (Functional Technique)mentioning
confidence: 99%
“…The contrast in the resulting images results from differing signal loss from hydrogen proton movement12. DWI has extensively been used in tumor grading34, early detection or differential diagnosis of benign and malignant tumors5678, distinguishing viable and necrotic tissues9101112, assessment of organ function13, prediction of pathologic outcomes1415, and evaluation of tumor response to therapies16171819.…”
mentioning
confidence: 99%